Strengthening Career Literacy for 12th Grade Students through Career Training and Information Services at SMA Negeri 1 Paya Pasir - Ali Daud Hasibuan; Harya Fitrida Lubis; Sri Nita Yani Sihombing; Husnul Khotimah; Amalia Azrina Sirgar (Generasi Sains Indonesia, 2025)
The Career Literacy Strengthening Activities for 12th Grade Students through Training and Career Information Services at SMA Negeri 1 Paya Pasir were conducted as a form of community service aimed at increasing students' awareness, understanding, and career readiness ahead of graduation. The background of this activity stems from students' low understanding of their potential, further educational pathways, and job prospects that match their interests and abilities. The activities were carried out through a participatory approach using interactive training methods and career information services, presented in the form of discussions, simulations, and self-reflection. The implementation of this activity involved Guidance and Counseling teachers, lecturers, university students, and 12th-grade students as the main participants. The results of the activity indicate that students experienced improvements in career awareness, decision-making abilities, and self-confidence in determining their future direction. In addition, this activity also contributed positively to enhancing the quality of career guidance services at school. Nevertheless, the activity still has limitations in terms of implementation time and participant coverage. Therefore, it is recommended that similar programs be conducted continuously with adequate facility support and collaboration with external parties such as universities and the workforce. Overall, this activity successfully strengthened students' career literacy and serves as a strategic step in preparing a young generation that is independent, visionary, and ready to face future workforce challenges.